Efeitos da intoxicação e abstinência de etanol sobre os parâmetros neuroinflamatórios em regiões mesencefálicas relacionadas à ansiedade em ratos - Bonassoli, Vivian Taciany (2014)
This study was aimed to investigate the effects of ethanol intoxication and withdrawal on neuroinflammatory parameters in dorsolateral periaquedutal gray matter (DLPAG) and dorsal raphe nucleus (DRN) in rats, as well to evaluate the effects of nitric oxide synthase (NOS) inhibition on ethanol withdrawal-induced anxiety. In the first chapter, we investigated whether the effects of ethanol intoxication and withdrawal on microglial activation and NOS inducible (iNOS) expression in DLPAG and NDR; cytokines levels in midbrain and effects of iNOS inhibitor, N-([3-(aminomethyl)phenyl] methyl) ethanimidamide dihydrochloride (1400W) on ethanol withdrawal-induced anxiety-like behaviour. Male Wistar rats were forced to consume a liquid diet containing ethanol 6 8 % (v/v) for 15 days as their only source of diet, then their behavior were tested immediately after last exposure (intoxicated) or 24 h ethanol withdrawal (WD). The control group received the same diet with sucrose instead ethanol for energetic balance. Three days before diet exposure ends, started treatment with (Sal) i.p. for intoxicated and control groups; and Sal or 1400W for withdrawn group (WD), which was subdivided in 4 subgroups: WD+Sal, WD+1400W 0,75; 1,5 or 3,0 μg/kg. The treatment persisted until testing day. OX-42 and iNOS expression were evaluated by immunohistochemistry and cytokines levels (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, TNF-α, IFN-γ e GM-CSF) were analyzed by Luminex xMAP. Ethanol withdrawal (WD+Sal) promoted an anxiogenic-like effect compared to control. Treatment with 1400W 1,5 μg/kg decreased the anxiogenic-like effect induced by ethanol withdrawal. Intoxicated group showed OX-42 and iNOS expression increased, while WD+Sal showed only OX-42 increased in both regions compared with control. 1400W administration did not alter OX-42 or iNOS. Cytokine levels were not altered in any experimental groups. There results suggest ethanol intoxication promotes an inflammatory state in DLPAG and DRN, which may be related with ethanol withdrawal-induced anxiety-like behavior. In the second chapter, we investigated whether nitric oxide (NO) in the DLPAG is involved in the expression of ethanol withdrawal-induced anxiety-like behaviour. Male Wistar rats were implanted with guide cannulae aimed at the DLPAG. The animals were forced to consume a liquid diet containing ethanol 6 8 % (v/v) for 15 days as their only source of diet. Six days after surgery and 24 h after ethanol discontinuation, the animals received microinjections of the NO scavenger 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (carboxy-PTIO), nonselective nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME), selective neuronal nitric oxide synthase inhibitor 1-(2-trifluoromethyl]phenyl) imidazole (TRIM), selective inducible nitric oxide synthase (iNOS) inhibitor N-([3-(aminomethyl)phenyl] methyl) ethanimidamide dihydrochloride (1400W) or saline into the DL PAG. Ten minutes later, the animals were tested in the light/dark box and open field. Carboxy-PTIO (1 nmol), L-NAME (200 nmol), TRIM (20 nmol), and 1400W (0,3 and 1 nmol) decreased the anxiogenic-like effects of ethanol withdrawal in rats in the light/dark box test. The NO precursor L-arginine reversed the effects of L-NAME. These results suggest NO production in the DLPAG may play a role in the modulation of ethanol withdrawal-induced anxiety-like behavior in rats. Furthermore, iNOS-mediated NO synthesis in the DLPAG is predominantly involved in the behavioral expression of anxiety-like behavior during ethanol withdrawal.